2021
DOI: 10.26529/cepsj.1126
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Remote Pandemic Education on Crafts Pedagogy: Opportunities, Challenges, and Interaction

Abstract: The Covid-19 pandemic caused many sudden social changes, including a shift to remote education in many countries. In Finland, remote education also concerns crafts as a standard school subject, combining aspects of art, design, textile, and technology in basic education. Accordingly, Finnish craft teachers faced the unprecedented situation of teaching remotely a subject, which often involves hands-on activities with tangible tools and materials. The present study explores how craft pedagogy has been adapted to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
7
0
6
Order By: Relevance
“…The pandemic showed that CHIs and creative communities are considering becoming more active online through podcasts, live content, and game creation; e.g., 40% of the museums increased online visits when closed, and 41% increased visits when they re-opened due to online engagement during the pandemic [72,73]. At the same time, people involved in craft training and craft production have adapted their strategies by intelligently applying ICT technologies to provide online tutoring [74] and employing digital marketing to enhance the visibility and availability of their products online [75].…”
Section: Lessons Learned From the Covid-19 Pandemicmentioning
confidence: 99%
“…The pandemic showed that CHIs and creative communities are considering becoming more active online through podcasts, live content, and game creation; e.g., 40% of the museums increased online visits when closed, and 41% increased visits when they re-opened due to online engagement during the pandemic [72,73]. At the same time, people involved in craft training and craft production have adapted their strategies by intelligently applying ICT technologies to provide online tutoring [74] and employing digital marketing to enhance the visibility and availability of their products online [75].…”
Section: Lessons Learned From the Covid-19 Pandemicmentioning
confidence: 99%
“…Indeed, the curriculum of crafts in basic education directs using digital means for designing, documenting, and assessing craft processes (FNBE, 2016). Fortunately, this background helped craft teachers to adapt their teaching to remote pedagogy as the pandemic hit the world (Kouhia, Kangas & Kokko, 2021).…”
Section: The Changing Subject: Crafts and Craft Education In A State ...mentioning
confidence: 99%
“…In our previous study on remote pandemic craft education (Kouhia, Kangas & Kokko, 2021), we analyzed experiences and reports about learning and teaching crafts during the Covid-19 pandemic, shared by 123 craft educators representing craft teachers mainly from basic education but also from other institutions, such as vocational training and non-formal adult education. We conducted an inductive qualitative coding of the data consisting 27 groupwork documents produced by the educators participating in two craft webinars on remote craft pedagogy in autumn 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this process applies when normal face-to-face learning or Distance Learning (PJJ) takes place during the pandemic. However, PJJ is more teacher-centered and task-oriented than classroom interaction [5].…”
Section: Introductionmentioning
confidence: 99%